Cultural Barriers of International Students Employability in Japan (Comparative & International Education Series, 2022)
This chapter discusses the employability for international students who partake in a full time English-Taught Program (ETP) in Japan. The empirical analysis of this study was designed by means of text-mining analysis. The data collection was conducted from 24 students who originate from the Global South countries. Survey results showed that participants felt the cultural barriers faced at work and barriers in daily life regarding prospective employment in Japan. Working barriers were corporate culture, communication with colleagues, relationship between foreign and Japanese colleagues, and a gender disparity in the workplace were noted as significant. Daily life barriers were maintaining a work-life balance and the difficulty of building interpersonal relationships outside of work due to being a foreigner.